THE IMPORTANCE OF A MULTIDISCIPLINARY DIAGNOSTIC AND THERAPEUTIC APPROACH TO PAINFUL SYMPHYSIS SYNDROME IN ATHLETES - Vukosavljević, Katarina; Bojović, Miloš; Drljačić, Dragana; Vukušić, Kristina (Srpski medicinski časopis Lekarske komore, 2022)
Painful symphysis syndrome (pubalgia) in athletes is a particular injury, a painful condition, and dysfunction of the femoroinguinal region, which occurs due to the disproportion in strength between the abdominal wall muscles and the muscles of the lower extremities. This study aims to theoretically analyze the importance of a multidisciplinary diagnostic and therapeutic approach to painful symphysis syndrome in athletes. More than seventy causes of pubalgia have been presented in literature, most commonly linked to sports factors. Activities that include repetitive strong kicks, rotational movements, circumduction, and torsion, are risk factors. The syndrome was first registered in football players, and it mostly occurs in male athletes under the age of forty. Establishing a diagnosis is difficult,due to the complex anatomy and the overlapping of symptoms between different groin injuries. The therapeutic approach depends on the complexity of the injuries and the dynamics of the patient’s recovery. It entails observing the principles of initiating treatment with minimally invasive modalities and reserving surgical treatment as the final therapeutic option, after which it is necessary to conduct an appropriate rehabilitation program, tailored to the pain and the dynamics of recovery. Most athletes resume their sports activities after two to three months, with no recurrence of pubalgia after surgical treatment. However, bearing in mind that the occurrence of pubalgia prevents the patients from engaging in sports activities over a prolonged period, special attention should be directed towards the prevention of this painful syndrome. Taking this into consideration, prevention should begin at the earliest age, through a daily program of exercises for strengthening the muscles of the anterior abdominal wall, with special emphasis on the oblique and transverse abdominal muscles.